Effects of a culturally adapted group based Montessori based activities on engagement and affect in Chinese older people with dementia: a randomized controlled trial - Chan, Helen Yue-lai (BMC Geriatr, 2021)
BACKGROUND: The Montessori Method underpinned by the principle of person-centered care has been widely adopted to design activities for people with dementia. However, the methodological quality of the existing evidence is fair. The objectives of this study are to examine the feasibility and effects of a culturally adapted group-based Montessori Method for Dementia program in Chinese community on engagement and affect in community-dwelling people with dementia. METHODS: This was a two-arm randomized controlled trial. People who were aged 60 years or over and with mild to moderate dementia were recruited and randomly assigned to the intervention group to receive Montessori-based activities or the comparison group to receive conventional group activities over eight weeks. The attendance rates were recorded for evaluating the feasibility. The Menorah Park Engagement Scale and the Apparent Affect Rating Scale were used to assess the engagement and affect during the activities based on observations. Generalized Estimating Equation model was used to examine the intervention effect on the outcomes across the sessions. RESULTS: A total of 108 people with dementia were recruited. The average attendance rate of the intervention group (81.5%) was higher than that of the comparison group (76.3%). There was a significant time-by-group intervention effect on constructive engagement in the first 10 minutes of the sessions (Wald χ(2) = 15.21–19.93, ps = 0.006–0.033), as well as on pleasure (Wald χ(2) = 25.37–25.73, ps ≤ 0.001) and interest (Wald χ2 = 19.14–21.11, ps = 0.004–0.008) in the first and the middle 10 minutes of the sessions, adjusted for cognitive functioning. CONCLUSIONS: This study provide evidence that Montessori-based group activities adapted to the local cultural context could effectively engage community-dwelling Chinese older people with mild to moderate dementia in social interactions and meaningful activities and significantly increase their positive affect. TRIAL REGISTRATION: ClinicalTrials.gov, NCT04352387. Registered 20 April 2020. Retrospectively registered.